Quantum interaction : 8th International Conference, QI 2014, Filzbach, Switzerland, June 30-July 3, 2014. Revised selected papers /: 8th International Conference, QI 2014, Filzbach, Switzerland, June 30-July 3, 2014. Revised selected papers. (2015) - Unknown
No abstract available